ANALISIS KONDISI PEMUKIMAN PENDUDUK DALAM PERTUMBUHAN EKONOMI INDONESIA - TEGUH SANTOSA; RINOVIAN RAIS (Institut Bisnis Muhammadiyah Bekasi, 2020)
In almost all countries there is a lot of discussion about population settlements as well as in this study researchers used the results of study materials discussed about settlements in other countries with those in indonesia, there were two research findings, namely the process by which people purchase and consume products and services to satisfy their needs, urban also neighborhood arrangement, which also scientific conditions are in accordance also condition of including indonesia state, there are also some qualities of limited human strenght and many types of housing available in Indonesia’s infrastructure from the interaction of the commmunity in the public sector